Ketamine induces immediate and delayed alterations of OCD-like behavior - Thompson, Summer L.; Welch, Amanda C.; Iourinets, Julia; Dulawa, Stephanie C. (Psychopharmacology, 2020)
Rationale: Obsessive-compulsive disorder (OCD) is a psychiatric disorder characterized by intrusive obsessive thoughts and/or compulsive behaviors. Currently, serotonin reuptake inhibitors (SRIs) provide the only pharmacological monotherapy for OCD, but response rates are insufficient. Ketamine, a noncompetitive NMDA receptor antagonist, was reported to have rapid, sustained therapeutic effects in OCD patients. However, the mechanisms remain unknown. Objectives: Here, we aimed to provide a platform for investigating mechanisms underlying anti-OCD effects of ketamine treatment by assessing whether ketamine pretreatment could alleviate 5-HT1B receptor (5-HT1BR)-induced OCD-like behavior in mice. Methods: We assessed whether acute ketamine (0, 3, 10, 30 mg/kg), administered at two pretreatment time points (30 min, 24 h), would modulate 5-HT1BR-induced OCD-like behavior in mice. Behavioral measures were perseverative hyperlocomotion in the open field and deficits in prepulse inhibition (PPI) induced by acute pharmacological 5-HT1BR challenge. Results: Three milligrams per kilogram of ketamine reduced 5-HT1BR-induced perseverative hyperlocomotion, but not PPI deficits, 24 h postinjection. In contrast, higher doses of ketamine were either ineffective (10 mg/kg) or exacerbated (30 mg/kg) 5-HT1BR-induced perseverative hyperlocomotion 30 min postinjection. At 24 h postinjection, 30 mg/kg ketamine reduced perseverative hyperlocomotion across all groups. Conclusions: Our results suggest that the 5-HT1BR-induced model of OCD-like behavior is sensitive to a low dose of ketamine, a potential fast-acting anti-OCD treatment, and may provide a tool for studying mechanisms underlying the rapid therapeutic effects of ketamine in OCD patients. (PsycInfo Database Record (c) 2022 APA, all rights reserved)
Keywords: 5-HT1B; Animal Behavior; Animal Open Field Behavior; Compulsions; Compulsive; Ketamine; Mice; N-Methyl-D-Aspartate; NMDA; OCD; Obsessive Compulsive Disorder; Perseveration; Perseverative; Prepulse Inhibition; Prepulse inhibition; RU24969